Comparative Efficacy and Safety of Anticoagulation Therapy in the Management of Patients with Concurrent Pulmonary Embolism and Atrial Fibrillation: A Systematic Review and Meta-Analysis - Aurangzeb, Laraib; Ahmad, Jawad; Zeb, Aimen; Wahab, Qazi Muhammad Farooq; Muhammad Ayub,; Afridi, Aibad Ahmed; Qasim, Hamad; Tahir, Haroon; Hussain, Ijaz; Khan, Shah Faisal; Noor, Muhammad Amin; Zahid, (Indus Journal of Bioscience Research, 2025)
Background: Management of anticoagulation in patients with both pulmonary embolism (PE) and atrial fibrillation (AF) can be difficult. They also continue to be at a higher risk of embolic events including stroke and recurrent pulmonary embolism, but at the same time remain at a high risk of bleeding secondary to anticoagulation. Management of this dual diagnosis complicates the administration and dosing of anticoagulant medications with the dual aim of preventing thromboembolic events while at the same time not increasing the risk of haemorrhage. Objectives: The current meta-analysis and systematic review was designed to compare and assess the effectiveness and safety of DOACs compared to warfarin in individuals with both PE and AF with reference to TE, stroke risk, and bleeding. Methods: A PubMed, Cochrane Library, and Scopus search was performed for all articles comparing different anticoagulation regimes in the patients with both PE and AF. Inclusion criteria were RCTs and cohort studies of patients from 2010 to 2023. Meta-analysis used fixed/fixed or random/random models and efficacy and safety outcomes were estimated by RR and 95% CI. Results: DOACs were also reported to prevent recurrent PE (RR = 0.58, 95% CI [0.40–0.85]) and ischemic stroke (RR = 0.58, 95% CI [0.35–0.93]). Furthermore, DOACs was associated with less major bleedings (RR = 0.52; 95% CI [0.32–0.85] and intracranial hemorrhage (RR = 0.30; 95% CI [0.11–0.83]. Conclusion: Certain DOACs are superior to warfarin in the treatment of anticoagulation in patients with both PE and AF making the use of DOACs a possible pathway towards the management of both thromboembolic events and bleeding complications. These findings add credence to the general use of DOACs over the current traditional treatment in this high-risk group.